A genetic algorithm for shortest path with real constraints in computer networks - Fahad. A. Alghamdi; Ahmed Younes Hamed; Abdullah M. Alghamdi; Abderrazak Ben Salah; Tamer Hashem Farag; Walaa Hassan (Institute of Advanced Engineering and Science, 2023)
The shortest path problem has many different versions. In this manuscript, we proposed a muti-constrained optimization method to find the shortest path in a computer network. In general, a genetic algorithm is one of the common heuristic algorithms. In this paper, we employed the genetic algorithm to find the solution of the shortest path multi-constrained problem. The proposed algorithm finds the best route for network packets with minimum total cost, delay, and hop count constrained with limited bandwidth. The new algorithm was implemented on four different capacity networks with random network parameters, the results showed that the shortest path under constraints can be found in a reasonable time. The experimental results showed that the algorithm always found the shortest path with minimal constraints.